2012
DOI: 10.1111/j.1740-8709.2012.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an educational intervention to improve child feeding practices and growth in rural China: updated results at 18 months of age

Abstract: Inappropriate complementary feeding practices have led to, in part, significant disparities in growth and nutritional status between rural and urban children in China. A cluster-randomised, controlled trial was implemented in Laishui, China to assess the effectiveness of an educational intervention on caregivers' feeding practices and children's growth. Eight townships were randomly assigned to the intervention or control. Five hundred ninety-nine healthy infants were enrolled at 2-4 months old, and were follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 18 publications
6
50
0
2
Order By: Relevance
“…They provided nutritional counseling without food supplements and reported results similar to ours [15][16][17]. They provided nutritional counseling without food supplements and reported results similar to ours [15][16][17].…”
Section: Discussionsupporting
confidence: 75%
“…They provided nutritional counseling without food supplements and reported results similar to ours [15][16][17]. They provided nutritional counseling without food supplements and reported results similar to ours [15][16][17].…”
Section: Discussionsupporting
confidence: 75%
“…Almost all mothers in the intervention group had good knowledge about the bene ts of pulses, household food processing techniques, and methods of preparation; they also started preparing complementary food using pulse crops. This current study ndings are similar to other large intervention studies in other counties such as China [30,31] and Kenya [32], which showed improved mothers' knowledge about feeding practices when health service providers were used to provide nutrition education.…”
Section: Discussionsupporting
confidence: 89%
“…There is evidence that the ICFI score is positively correlated with infant nutritional status in underprivileged population groups . However, the use of the ICFI to measure the impact of an intervention programme on children's eating practices has only been reported by Zhang , with adaptations according to recommendations for Chinese children. Higher ICFI scores were observed for the intervention group at all ages, as evaluated between 6 and 18 months.…”
Section: Discussionmentioning
confidence: 99%